The structure and dynamic of the defensive organization the personality in Paranoid Schizophrenia, Schizoaffective and Affective Disorders - I M Kadyrov; A A Оksimetz (Peoples' Friendship University of Russia (RUDN University), 2011)
The article suggests a research model and discusses results of an empirical study of the defensive organization mechanisms of patients diagnosed with paranoid schizophrenia, schizoaffective and affective disorders. The research deals with structural and dynamic aspects of the defensive organization profiles in the mentioned three clinical groups.